Islamic Values in ELT for Teachers of Primary Education - Al-Manduriy, Shahibul Muttaqien (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2021)
The majority of education today are adapted from well-develop countries such as western world. The western world is a world that fostering the knowledge and science that not suitable with the Islamic live and values. The primary education is the starting education for the human live in their education. The students of Primary education are fresh minded so the knowledge they receive will root in their mind. English language teaching is one of the few subjects which is taught in Primary Education, this subject is crucial and need more attention for the teachers who are teaching in primary education because the originality of this language is from the western world. Therefore, the integration of Islamic values to teach this subject is highly recommended for the teachers of ELT in Primary Education